Gender across Media Landscapes - Kamińska, Aleksandra; Kowal, Ewa; O'Toole, Olga (Critical Studies, 2026)
The end of the first quarter of the 21st century invites us to revisit what gender means in society and how it has shaped our literal and cultural landscapes. This volume seeks to explore these spaces from interdisciplinary perspectives. The contributions span both "highbrow" art and popular culture, mapping interactions between gender and landscape as represented through numerous media. From urban to wild landscapes, distant planets, but also discursive practices, gendered domesticity, and the landscape of the body, the reader is invited to reflect on gender as a ubiquitous cultural marker. While contributing to the growing body of work on gender, media, and landscape, the volume lays out a new groundwork for developments in interdisciplinary studies on gender and its possible futures.